A map of cell type‐specific auxin responses - Bargmann, Bastiaan O R; Vanneste, Steffen; Krouk, Gabriel; Nawy, Tal; Efroni, Idan; Shani, Eilon; Choe, Goh; Friml, Jiří; Bergmann, Dominique C; Estelle, Mark; Birnbaum, Kenneth D (Molecular systems biology, 2013)
In plants, changes in local auxin concentrations can trigger a range of developmental processes as distinct tissues respond differently to the same auxin stimulus. However, little is known about how auxin is interpreted by individual cell types. We performed a transcriptomic analysis of responses to auxin within four distinct tissues of the Arabidopsis thaliana root and demonstrate that different cell types show competence for discrete responses. The majority of auxin‐responsive genes displayed a spatial bias in their induction or repression. The novel data set was used to examine how auxin influences tissue‐specific transcriptional regulation of cell‐identity markers. Additionally, the data were used in combination with spatial expression maps of the root to plot a transcriptomic auxin‐response gradient across the apical and basal meristem. The readout revealed a strong correlation for thousands of genes between the relative response to auxin and expression along the longitudinal axis of the root. This data set and comparative analysis provide a transcriptome‐level spatial breakdown of the response to auxin within an organ where this hormone mediates many aspects of development. The transcriptional response to auxin was analyzed in four root cell types. The newly obtained data were cross‐referenced with spatial expression maps to examine auxin's role in regulating gene expression in the root meristem. Synopsis The transcriptional response to auxin was analyzed in four root cell types. The newly obtained data were cross‐referenced with spatial expression maps to examine auxin's role in regulating gene expression in the root meristem. The majority of the thousands of auxin‐responsive genes in the Arabidopsis thaliana root show a spatial bias in their induction or repression by auxin treatment. Auxin promotes the expression of cell‐identity markers for the developing xylem and quiescent center, whereas it inhibits markers for the maturing xylem, cortex and trichoblasts. Relative induction or repression by auxin predicts expression along the longitudinal axis of the root.